1903 S.D. Rev. Codes 1150, Penal Code 1150, § 469. - (:unkn) unknown (General Publisher, 1903)
. Every person who manufactures or causes to be manufactured, or sells or offers or keeps for sale, or gives or disposes of any instrument or weapon of the kind usually known as slung shot, or of any similar kind is guilty of a misdemeanor.
--
Keywords: TRANSFER; MANUFACTURE & POSSESSION - NON-GUN ARMS